President’s Message - McKay, Marcy (Operating Room Nurses Association of Canada Journal, 2006)
I love this time of year. I love the colours and the smell of autumn in the air. Perhaps it is a holdover from my student days when the new school year began in September, but I have always seen it as the start of something new!